Attenuation of the cardiovascular response during rigid bronchoscope a comparative study using intravenous lidocaine and sublingual glyceryl trinitrate - Muhanad A. Ahmed (مجلة كلية الطب, 2011)
Background: one of the complications of rigid bronchoscope is the cardiovascular responses that may carry a dangerous drawback during and after the procedure. Prevention and control of these events will be crucial, especially for the old and cardiovascular debilitated patients. Objective: The study aims to control and attenuate the unwanted hemodynamic responses to the rigid bronchoscpe using intravenous lidocaim and GTN. Method: a study was performed on three groups of patients undergone a diagnostic procedure of bronchoscope. Each group consists of 20 patients at the same age and relatively similar pathology. The three groups (group one, two and three) received lidocaine, glyceryltrinitrate and no drug respectively. The changes in mean arterial pressure, heart rate and rhythm were taken and monitored. Several readings were taken through a five to ten minutes interval and at recovery. The doses are calculated equally for all patients. Results: marked changes were noticed in mean arterial pressure which has been increased especially during the introduction of the instrument through the trachea. The same were happened for the heart rate, which increased tremendously at the same intervals. The same was applied for the rhythm. Lidocaine has attenuate the change in the rhythm, while the glyceryl trinitrate prevented the high elevation in mean arterial blood pressure more than the other drug did. Conclusion: Hemodynamic responses to the rigid bronchoscope, can be attenuated and blunted by the usage of anti-arrhythmic drug (lidocaine) and the vasodilator glyceryl-trinitrate, intravenously and sublingual respectively. Lidocaine I.V given 3 – 5 minutes prior to the procedure will protect the heart from grand changes in its rhythm. And to a lesser extent control the high elevation in mean arterial pressure. Glyceryl-trinitrate (GTN). The two drugs successfully attenuate the hemodynamic responses to the tracheal instrumentation by the rigid bronchoscope.